Prevalence of pre-diabetes and undiagnosed diabetes in the Mollerussa prospective observational cohort study in a semi-rural area of Catalonia - Falguera, Mireia (BMJ Open, 2020)
OBJECTIVES: To assess the prevalence of undiagnosed diabetes and pre-diabetes in the healthy population in the Mollerussa cohort. As a secondary objective, to identify the variables associated with these conditions and to describe the changes in glycaemic status after 1 year of follow-up in subjects with pre-diabetes. DESIGN: Prospective observational cohort study. SETTING: General population from a semi-rural area. PARTICIPANTS: The study included 583 participants without a diagnosis of diabetes recruited between March 2011 and July 2014. RESULTS: The prevalence of undiagnosed diabetes was 20, 3.4% (95% CI 2.6 to 4.2) and that of pre-diabetes was 229, 39.3% (37.3 to 41.3). Among those with pre-diabetes, 18.3% had isolated impaired fasting plasma glucose (FPG) (FPG: 100 to <126 mg/dL), 58.1% had isolated impaired glycated haemoglobin (HbA1c) (HbA1c 5.7 to <6.5) and 23.6% fulfilled both criteria. Follow-up data were available for 166 subjects; 41.6%(37.8 to 45.4) returned to normoglycaemia, 57.6% (57.8 to 61.4) persisted in pre-diabetes and 0.6% (0 to 1.2) progressed to diabetes. Individuals with pre-diabetes had worse cardiometabolic risk profiles and sociodemographic features than normoglycaemic subjects. In the logistic regression model, variables significantly associated with pre-diabetes were older age (OR; 95% CI) (1.033; 1.011 to 1.056), higher physical activity (0.546; 0.360 to 0.827), body mass index (1.121; 1.029 to 1.222) and a family history of diabetes (1.543; 1.025 to 2.323). The variables significantly associated with glycaemic normalisation were older age (0.948; 0.916 to 0.982) and body mass index (0.779; 0.651 to 0.931). CONCLUSIONS: Among adults in our region, the estimated prevalence of undiagnosed diabetes was 3.4% and that of pre-diabetes was 39.3%. After a 1-year follow-up, a small proportion of subjects (0.6%) with pre-diabetes progressed to diabetes, while a high proportion (41.6%) returned to normoglycaemia. Individuals with pre-diabetes who returned to normoglycaemia were younger and had a lower body mass index.